Nuclear quadrupole double resonance - Mailer, J (1977)
﻿ The basic theories of Nuclear Quadrupole Resonance are outlined, together with some basic NMR theory and its application to double resonance techniques. An improved design of spectrometer using double resonance is presented, including a description of a new flow cryostat which can operate down to 4.2°K with low (250 cc/hour) consumption of liquid He. The whole apparatus may be used to detect NQR signals in solids over the frequency range 100 kHz-5 MHz. The theory of double resonance with spin mixing by continuous coupling (D R CC) is developed and illustrated by experiments performed on HCOOD, HDO and several nitrogen-containing compounds, including Imidazole. Further experiments were then carried out on samples dilute in deuterium, including the detection of NQR in formic acid (HCOOH) due to naturally abundant deuterium. Other experiments on proton-deuteron interactions in amide groups and in water molecules are also described and compared with results previously published on fully-deuterated amides and D20 as a water of crystallisation in L-serine hydrate. The NQR spectrum of Lanthanum Nicotinate Dihydrate is obtained using F.M. techniques and related to its structure. The theory of Zeeman NQR in spin 3/2 nuclei is developed with reference to the double resonance technique, and the measured quadrupole coupling constants of 23Na and 2D in NaOH and some of its hydrates are discussed. Finally, some standard theories concerning proton relaxation times in solids at low temperatures (4°K-300°K) are outlined and related to some, measured relaxation times, illustrating their significance to the double resonance technique. The concluding chapter outlines a speculative proposal for a new spectrometer design.